Specific Manifestations of Tuberculosis Infection in Different Age Groups in Children and Adolescents according to Results of Screening with 2 Intradermal Tests (with Tuberculin and Tuberculous Recombinant Allergen (CFP10-ESAT6)) in Moscow in 2023 - L. V. Slogotskaya; E. M. Bogorodskaya; L. F. Shamuratova; T. A. Sevostyanova; D. A. Kudlay; N. Yu. Nikolenko (Туберкулез и болезни лёгких)
The objective: to assess eﬀectiveness of mass screening for tuberculosis infection in children and adolescents in Moscow, determine infection rate and incidence in diﬀerent age groups.Subjects and Methods. Screening was performed in 2023. Two diﬀerent screening methods were used in diﬀerent ages: all children aged 0 to 7 years were given Mantoux test with 2 TU PPD-L, and if the reaction increased versus the previous year, a test with tuberculous recombinant allergen (Diaskintest or TRA) was performed additionally. Children and adolescents aged 8-17 years were given the TRA test only. Mantoux test was used in 729,972 children from 0 to 7 years old. Positive responses were observed in 488,706 (66.9%) of them, which was due to the high rate of post-vaccination allergies at that age. When tuberculosis infection was suspected, the TRA test was performed in 21,552 people. (4.4% of all tuberculin-positive individuals). At the same time, positive reactions were noted in 201 people (0.9%). Among them, tuberculosis was detected in 7.5% (15 patients), post-tuberculosis changes (the calciﬁcation phase of the disease) were detected in 8.5% (17 people), while the proportion of positive reactions to the TRA test increased. Children of 8-17 years old were screened with the TRA test only. 1,170,461 people were examined, positive reactions were noted in 0.2%. The detection rate of tuberculosis among them was 1.6% (30 people), and the rate of the calciﬁcation phase of the disease indicating spontaneous recovery was 3.7%. The proportion of positive reactions is growing as the age of children increases, which corresponds to the higher incidence of pulmonary tuberculosis at these ages. The analysis of the incidence of various forms of tuberculosis in Moscow revealed the following. At the age of up to 7 years, tuberculosis of the lymphatic system predominates and this is the period with the highest incidence of this form. Then in the period before puberty, the lowest incidence is observed. After that, pulmonary forms of tuberculosis begin to predominate, and in adolescence, the incidence rises to maximum rates. BCG vaccination in the neonatal period resulted in the near disappearance of tuberculosis mortality, and such forms as miliary tuberculosis and meningitis. However, BCG vaccination and revaccination could not prevent pulmonary forms of tuberculosis in adolescence. The article presents age-speciﬁc mortality rates in Moscow in the pre-antibacterial era, when BCG vaccination was not available and the predominant forms of tuberculosis at diﬀerent ages were the cause of death.Results: Obviously, a one-stage screening (TRA test) performed in children of 8-17 years old, is more convenient for both medical workers and patients, and it is more cost eﬀective. However, it is currently impossible to switch to this test when examining children under 7 years, since children receive BCG revaccination if the response to Mantoux test is negative.